Genotypic diversity evaluation for nutritional and grain quality attributes in cultivated rice varieties of Assam - Thakur, Kangkana; Kalita, Mridusmita; Saharia, Daizi Durba; Sarma, Nayanika; Sarma, M. K.; Banu, Sofia (Current Botany, 2025)
A set of fifty rice genotypes mostly of indigenous type and a few improved varieties grown by farmers of Assam were studied to screen for nutritional content, grain characteristics and yield potential. Based on the grain classification system, two cultivars were categorised as small (1.5-2), eleven were medium (2.1-2.5), fourteen had medium slender (2.6-3.0) grain, and eighteen were of slender (>3.0) type; Mahsuri had the highest grain yield per plant (49.64 g). The glutinous type, ‘Bora’ group of cultivars had comparatively the lower content of amylose (2.45-2.76%) with corresponding higher level of amylopectin (97.24-97.55%). A wide variation was observed for protein content, ranging from 3.5% in Amona Bao to 12.26% in Vandana. Manipuri Joha and Badol Sali were found to have the greatest concentrations of iron (466.88 mg/100 g) and zinc (44.8 mg/100 g), respectively. Grain length breadth ratio, volume expansion ratio, iron and protein content showed significant positive correlation with grain yield. High heritability in the broad sense was observed for the traits grain weight, grain length and breadth, length: breadth ratio, volume expansion ratio, iron and zinc. The cultivars were categorized into six clusters based on the Mahalanobis D2 analysis, with cluster VI (739221) exhibiting the highest intra-cluster distance and cluster V with cluster II (27774001) exhibiting the highest inter-cluster distance. The genotypes belonging to the diverse clusters along with the desirable per se performance might be chosen for inclusion as parents in the hybridization program. Comprehensive understanding of the nutrients and grain characteristics and their relationship with grain yield would pave the way for further genetic improvement of quality and yield of rice.